2009
DOI: 10.1103/physreva.80.022328
|View full text |Cite
|
Sign up to set email alerts
|

Optimized pulses for the perturbative decoupling of a spin and a decoherence bath

Abstract: In the framework of nuclear magnetic resonance, we consider the general problem of the coherent control of a spin coupled to a bath by means of composite or continuous pulses of duration p . We show explicitly that it is possible to design the pulse in order to achieve a decoupling of the spin from the bath up to the third order in p . The evolution of the system is separated in the evolution of the spin under the action of the pulse and of the bath times correction terms. We derive the correction terms for a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(79 citation statements)
references
References 42 publications
4
75
0
Order By: Relevance
“…(25)] is reduced to only two constants. The parameter υ gives an effective pulse length to first order; it is equal to zero, υ = 0 for ideal δ-inversion pulses (rotation angle φ 0 = π), as well as for Hermitian pulses [53] or other 1st-order self-refocusing pulses [19,52,54]. The parameter υ 2 vanishes for ideal δ-pulses with the rotation angle φ 0 = π/2; for hard inversion pulses [Eq.…”
Section: Average Evolution Operator For a Single Pulsementioning
confidence: 99%
“…(25)] is reduced to only two constants. The parameter υ gives an effective pulse length to first order; it is equal to zero, υ = 0 for ideal δ-inversion pulses (rotation angle φ 0 = π), as well as for Hermitian pulses [53] or other 1st-order self-refocusing pulses [19,52,54]. The parameter υ 2 vanishes for ideal δ-pulses with the rotation angle φ 0 = π/2; for hard inversion pulses [Eq.…”
Section: Average Evolution Operator For a Single Pulsementioning
confidence: 99%
“…By expanding the final-time unitary evolution operator generated by H open with respect to t f H e and t f Γ about t f H e = 0 and t f Γ = 0, Pasini et al have identified controlfield criteria necessary to eliminate perturbative first-and second-order effects resulting from the environment Hamiltonian H e and the interaction term S · Γ [15]. Although applicable to multi-polarized controls and general qubit-environment coupling, the methodology developed in this section assumes control-qubit coupling along the z-axis and qubit-environment interaction along the x-axis, i.e.,…”
Section: A General Robustness Criteriamentioning
confidence: 99%
“…According to the analysis in ref. [15], when [H e , Γ λ ] = 0, for all λ, components η 4 and η 5 can be neglected from the vector constraint.…”
Section: A General Robustness Criteriamentioning
confidence: 99%
See 2 more Smart Citations